An α-Gal antigenic surrogate as a biomarker of treatment evaluation in Trypanosoma cruzi-infected children. A retrospective cohort study - Abal, Manuel (2024)
Background: Proper evaluation of therapeutic responses in Chagas disease is hampered by the prolonged persistence of antibodies to Trypanosoma cruzi measured by conventional serological tests and by the lack of sensitivity of parasitological tests. Previous studies indicated that tGPI-mucins, an α-Gal (α-d-Galp(1→3)-β-d-Galp(1→4)-d-GlcNAc)-rich fraction obtained from T. cruzi trypomastigotes surface coat, elicit a strong and protective antibody response in infected individuals, which disappears soon after successful treatment. The cost and technical difficulties associated with tGPI-mucins preparation, however, preclude its routine implementation in clinical settings. Methods/principle findings: We herein developed a neoglycoprotein consisting of a BSA scaffold decorated with several units of a synthetic α-Gal antigenic surrogate (α-d-Galp(1→3)-β-d-Galp(1→4)-β-d-Glcp). Serological responses to this reagent, termed NGP-Tri, were monitored by means of an in-house enzyme-linked immunosorbent assay (α-Gal-ELISA) in a cohort of 82 T. cruzi-infected and Benznidazole- or Nifurtimox-treated children (3 days to 16 years-old). This cohort was split into 3 groups based on the age of patients at the time of treatment initiation: Group 1 comprised 24 babies (3 days to 5 months-old; median = 26 days-old), Group 2 comprised 31 children (7 months to 3 years-old; median = 1.0-year-old) and Group 3 comprised 26 patients (3 to 16 years-old; median = 8.4 years-old). A second, control cohort (Group 4) included 39 non-infected infants (3 days to 5 months-old; median = 31 days-old) born to T. cruzi-infected mothers. Despite its suboptimal seroprevalence (58.4%), α-Gal-ELISA yielded shorter median time values of negativization (23 months [IC 95% 7 to 36 months] vs 60 months [IC 95% 15 to 83 months]; p = 0.0016) and higher rate of patient negative seroconversion (89.2% vs 43.2%, p < 0.005) as compared to conventional serological methods. The same effect was verified for every Group, when analyzed separately. Most remarkably, 14 out of 24 (58.3%) patients from Group 3 achieved negative seroconversion for α-Gal-ELISA while none of them were able to negativize for conventional serology. Detailed analysis of patients showing unconventional serological responses suggested that, in addition to providing a novel tool to shorten follow-up periods after chemotherapy, the α-Gal-ELISA may assist in other diagnostic needs in pediatric Chagas disease. Conclusions/significance: The tools evaluated here provide the cornerstone for the development of an efficacious, reliable, and straightforward post-therapeutic marker for pediatric Chagas disease.